(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Since learning has often more to do with identification rather than with a simple transfer of information, I believe that teaching demands not only that one knows theoretically what the subject is about, but also that one intends to live up to what is being taught. This is especially the case in all teachings of social competence, as in the fields of human rights and peace education. In the following paper I would like to discuss this witha focus on spirituality, hence presuming that spirituality is a neglected factor in our Western culture in the field of human rights education and peace and democracy pedagogic. Furthermore I will establish a link between spirituality and freedom. I want to reflect on the idea and concept of freedom, asking whether a specific concept of freedom could be related to spirituality as its basic source.